An investigation into IgE-facilitated allergen recognition and presentation by human dendritic cells - Sharquie, Inas K.; Al-Ghouleh, Abeer; Fitton, Patricia; Clark, Mike R.; Armour, Kathryn L.; Sewell, Herb F.; Shakib, Farouk; Ghaemmaghami, Amir M. (BioMed Central, 2013)
Background: Allergen recognition by dendritic cells (DCs) is a key event in the allergic cascade leading to production of IgE antibodies. C-type lectins, such as the mannose receptor and DC-SIGN, were recently shown to play an important role in the uptake of the house dust mite glycoallergen Der p 1 by DCs. In addition to mannose receptor (MR) and DC-SIGN the high and low affinity IgE receptors, namely FcϵRI and FcϵRII (CD23), respectively, have been shown to be involved in allergen uptake and presentation by DCs.